Ultra-pure nanoporous gold films for electrocatalysis - Kwon, Hyunah; Barad, Hannah-Noa; Silva Olaya, Alex Ricardo; Alarcón Correa, Mariana; Hahn, Kersten; Richter, Gunther; Wittstock, Gunther; Fischer, Peer (ACS catalysis, 2023)
Nanoporous gold (Au) films are self-supported structures that possess a large surface area and extraordinary catalytic activity. Generally, nanoporous gold is obtained by solution-based dealloying where the less noble metal, often silver (Ag), is etched out. However, the residual amounts of the sacrificial metal are not well controlled, the impure samples show restructuring, and the residual metal prevents the study of the catalytic role of Au alone. Here, we fabricate impurity-free nanoporous gold films by a plasma-enabled dry synthetic route. The scheme does not include sacrificial metals or solution processing and is much more general. It is used to obtain self-supported ultra-pure nanoporous gold films with controllable pore sizes. The impurity-free nanoporous gold films possess highly curved ligaments, are remarkably robust, and stable over hundreds of electrochemical cycles. Furthermore, they contain many catalytically active sites, which is highly promising for electrocatalytic applications.